2002
DOI: 10.1023/a:1014444601158
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To evaluate the relative importance of clinicopathological factors affecting recurrence, progression, and survival in patients with superficial bladder cancer (pTa and pT1) undergoing bacillus Calmette-Guerin (BCG) therapy (Tokyo 172 strain), we reviewed data for 146 patients treated between 1985 and 1998. The median follow-up period was 64.7 months. Tumour recurrence, progression, and death were evaluated as endpoints using Cox's proportional hazards model. The 5-year recurrence-free rate was 56% for all 146 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Age has been recognized as the most important risk factor for development of bladder cancer, which is essentially a disease of the elderly; in our study, age showed to be associated with OS (HR 1.05, p = 0.002), but with none of the other endpoints. High tumour grade and T1 stage were found to be independent predictors of progression on multivariate analysis in a recent, large study by Fernandez-Gomez et al [16], but previous studies had failed to show such an association [17,18]. In our study, T stage was significantly associated with CSS, while it approached but did not reach statistical significance for progression (HR 3.51, p = 0.07).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Age has been recognized as the most important risk factor for development of bladder cancer, which is essentially a disease of the elderly; in our study, age showed to be associated with OS (HR 1.05, p = 0.002), but with none of the other endpoints. High tumour grade and T1 stage were found to be independent predictors of progression on multivariate analysis in a recent, large study by Fernandez-Gomez et al [16], but previous studies had failed to show such an association [17,18]. In our study, T stage was significantly associated with CSS, while it approached but did not reach statistical significance for progression (HR 3.51, p = 0.07).…”
Section: Discussioncontrasting
confidence: 55%
“…In the last years, a few clinical, pathological and molecular variables have been analysed in order to assess their role in predicting response to BCG [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. Reliable markers could help to identify patients at higher risk of BCG failure, worthy of undergoing early cystectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recycling of polymer waste materials and used polymers is one of the ways to conserve natural resources and to reduce environmental stress. The chemical degradation of polyurethanes—rigid, flexible, or polyurethane elastomers, involves well‐known methods of hydrolysis,1 glycolysis2–4 and aminolysis 5, 6…”
Section: Introductionmentioning
confidence: 99%
“…This multivariate analysis of four randomized CUETO trials included data from 1,062 patients with primary and relapsing high- and intermediate-risk tumors, showing a notable correlation between prior bladder cancer resections and recurrence [ 7 ]. Furthermore, Takashi et al [ 10 ] evaluated the prognostic significance of various clinicopathological factors that affect recurrence and progression in 146 patients with superficial bladder cancer undergoing BCG therapy and reported that patients with a past history of bladder cancer experienced significantly earlier recurrence than those without such history [ 10 ]. In the same way, Losa et al [ 11 ] found a connection between previous resections and recurrence in patients with non–muscle-invasive bladder tumor treated with adjuvant BCG immunotherapy.…”
Section: Discussionmentioning
confidence: 99%